Peter C. Petersen letter to Nicholas S. Halmi regarding bird sightings, February 13, 1977 - Petersen, Peter C.et al (1977)
Bird sightings contributed by Peter C. Petersen in a letter to Nicholas S. Halmi. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter, 1976-1977. Epson - sheet feed/flatbed